"They Scorned Us for Being What We Are": Irish identity, Civil Rights, and rhythm and blues on Cooke's Tour. Issue 4 (19th December 2017) - Farrell, Kevin
Abstract: This article explores the interplay between Irish identity and the American Civil Rights movement, focusing upon Sam Cooke's 1960 recording of "Galway Bay." Building from Lauren Onkey's "Celtic Soul Brother" concept, the study investigates Irish cultural, aesthetic, and political affinities for African American music while also seeking evidence that this affinity was reciprocated by black artists. While Cooke's recording of "Irish" material is typically considered in reference to his attempts to "cross over" and appeal to white audiences, the subtle political content of "Galway Bay" also offered surreptitious response to segregation and the Civil Rights demonstrations of the 1950s and early 1960s. By contextualizing this recording in reference to both its popular appeal and its political references, and considering both in light of Cooke's understanding of injustice and approach to advocacy, I attempt to re‐evaluate Cooke's major label debut album.